PENERAPAN METODE TOPSIS DALAM MENENTUKAN PEMILIHAN KARTU PRABAYAR HANDPHONE GOBAL SYSTEM FOR MOBILE (HP GSM) - Masitha, Masitha; Damanik, Irfan Sudahri; Windarto, Agus Perdana (STMIK Budi Darma, 2018)
Prepaid Card is a card that can only be used if there is a nominal number of pulses or data packets first. This card has an active period that varies depending on the policies and programs of each provider. Many card users are still confused about choosing a prepaid card that is good for use, so they really need information that can be used as a reference in choosing a prepaid card. In this study conducted to analyze a selection of prepaid cards using the TOPSIS (Technique For Order of Preference By Similarity To Ideal Solution) method in determining alternative choices for all prepaid card users, using several assessment criteria, namely: Cost (C1), Feature Completeness (C2), Signal (C3), Promotion / Advertising (C4), and Service Quality (C5). And also by using 6 alternatives, namely: Telkomsel (A1), Axis (A2), IM3 (A3), XL (A4), US (A5), and 3 (A6). And the results of this study were ranked first, namely: 3 (A6) as the first rank with a value of 0.5286 followed by XL (A4) with a value of 0.5238 as the second rank, and Telkomsel (A1) with a value of 0.5027. IM3 (A3) with a value of 0.4988, Axis (A2) with a value of 0.4765, then the last US (A5) with a value of 0.1905. It is hoped that this research can provide a better input to all prepaid card users.Keywords: TOPSIS, decision support system, pematang siantar, prepaid card